2006
DOI: 10.1300/j233v05n01_03
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Parenting in Drug Use Among Black, Latino and White Adolescents

Abstract: This study investigates the role of parenting in adolescent drug use for black, white and Latino adolescents. Parenting has been consistently identified as a crucial factor in drug use by adolescents. This study uses data from the National Longitudinal Study of Adolescent Health. Results show that parenting has a significant effect on drug use for these adolescents. The relationship between parenting and drug use is more strongly negative for the Latino adolescents, than for black and white adolescents. This i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 13 publications
4
42
0
Order By: Relevance
“…More attention has been paid to studying the link between parenting style/family environment and substance use, than has been paid to parenting style/family environment and gambling among college students (Adalbjamardottir & Hafsteinsson, 2001;AdamczykRobinette, Fletcher & Wright, 2002;Broman, Reckase & Freedman-Doan, 2006;Montgomery, Fisk & Craig, 2008;Patock-Peckham, et al, 2001;Patock-Peckham & Morgan-Lopez, 2006Wood, Read, Mitchell & Brand, 2004). Likewise, more is known about family environment and parenting as protective factors against problem behaviors among adolescents than among college students (Boyle & Boekeloo, 2009;Dane, Lawrence, Derevensky, McPhee & Panetta, 2008;Kelly et al, 2011;Marsiglia, Kulis, Parsai, Villar & Garcia, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…More attention has been paid to studying the link between parenting style/family environment and substance use, than has been paid to parenting style/family environment and gambling among college students (Adalbjamardottir & Hafsteinsson, 2001;AdamczykRobinette, Fletcher & Wright, 2002;Broman, Reckase & Freedman-Doan, 2006;Montgomery, Fisk & Craig, 2008;Patock-Peckham, et al, 2001;Patock-Peckham & Morgan-Lopez, 2006Wood, Read, Mitchell & Brand, 2004). Likewise, more is known about family environment and parenting as protective factors against problem behaviors among adolescents than among college students (Boyle & Boekeloo, 2009;Dane, Lawrence, Derevensky, McPhee & Panetta, 2008;Kelly et al, 2011;Marsiglia, Kulis, Parsai, Villar & Garcia, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…These researchers found that greater parental warmth and family acceptance exerted a stronger impact in reducing drug use among Latinos than among White and Black adolescents (4) . A study (22) reported that White students perceived parents as less authoritarian than…”
Section: Descritores: Comportamento Do Adolescente; Comportamentos Dementioning
confidence: 98%
“…Findings from numerous studies over the past 20 years suggest that the quality of the parent-adolescent relationship has significant impact on the development or prevention of risky adolescent health behaviors (1)(2)(3)(4)(5)(6)(7)(8) .…”
Section: Descritores: Comportamento Do Adolescente; Comportamentos Dementioning
confidence: 99%
“…Parents indeed played a key role in explaining adolescents' substance use (Broman, Reckase, & Freedman-Doan, 2006;Chassin, Curran, Hussong, & Colder, 1996;Hwang & Akers, 2006;Mebly et al, 1993;Simons & Robertson, 1989). Mebly et al (1993) reported that a mother's tobacco use significantly increased the risk of her children smoking.…”
Section: Peer Versus Parental Influencesmentioning
confidence: 99%